EXPERIMENTAL AND THEORETICAL STUDIES OF THE STABILITIES OF TALC, ANTIGORITE AND PHASE A AT HIGH PRESSURES WITH APPLICATIONS TO SUBDUCTION PROCESSES - Bose K.; Ganguly J. (My University, 1995)
We have experimentally determined the equilibrium talc # enstatite + quartz/coesite + H2O to 40 kbar in the system MgO-SiO2-H2O (MSH) using both synthetic and nearly pure Mg end-member natural talc and other synthetic starting materials for the other solid phases. At 40 kbar, the equilibrium dehydration boundary lies # 150°C higher than that calculated using data from the existing internally consistent thermochemical data bases. The reason for this discrepancy lies in the erroneous compressibility data of talc in the data bases. We have retrieved the compressibility of talc from the experimental phase equilibrium data, and have also calculated several other equilibria in the MSH system involving talc, antigorite and the dense hydrous magnesium silicate (DHMS), commonly referred to as phase A. Comparison of these equilibria with selected thermal profiles at the leading edge of young and old subducting oceanic slabs, along with the dehydration condition of basaltic amphibole and solidus of mantle peridotite, provides an explanation for the observed heights of the volcanic fronts above subducting oceanic lithosphere. Further, it is found that in cold oceanic slabs (=< 50 Ma with subduction velocity of =< 10 cm/y), antigorite will transform to the DHMS phase A through a vapor conserved reaction at a depth of # 200 km. Phase A will then serve as a carrier of water into the deeper mantle.